2003
DOI: 10.1081/jdi-120021158
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Clinical Outcome by Early Nephrology Referral in Type II Diabetics on Hemodialysis

Abstract: We demonstrate that the time of referral before starting dialysis is a predictor of survival for type II diabetics on HD. Patients with early referral are associated with longer survival. The beneficial effect might be associated with the timely initiation of the chronic HD program. These results suggest that early referral before dialysis is important in determining the long-term prognosis in type II diabetics on HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The studies reported findings from a wide range of countries: three studies from the UK, 236,237,273 a further four from Europe, 239,251,266,269 three from the USA, 249,277,352 five from Asia, 243,252,253,271,278 one from Australia/New Zealand 230 and one from Brazil. 270 All 17 studies were available in full publication.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies reported findings from a wide range of countries: three studies from the UK, 236,237,273 a further four from Europe, 239,251,266,269 three from the USA, 249,277,352 five from Asia, 243,252,253,271,278 one from Australia/New Zealand 230 and one from Brazil. 270 All 17 studies were available in full publication.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with a GFR < 20 ml/min/1.73 m² at first referral were grouped as 'late referral'. The remaining four studies 252,253,269,278 considered late referral as being referred less than 6 months prior to commencing RRT.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations